Association Between Serum Galectin-3 Levels and Coronary Stenosis Severity in Patients With Coronary Artery Disease - Li, Mingxing; Guo, Kai; Huang, Xuansheng; Feng, Li; Yuan, Yong; Li, Jiewen; Lao, Yi; Guo, Zhigang (Frontiers in Cardiovascular Medicine, 2022)
Background: The relationship between galectin-3 (Gal-3) and coronary artery disease (CAD) has not been fully elucidated. Aim: This study aimed to determine the relationship between the presence and severity of CAD and serum Gal-3 levels. Patients and Methods: 331 consecutive CAD patients were enrolled as the study group. An additional 62 patients without CAD were enrolled as the control group. Serum Gal-3 levels were separately compared between the non-CAD and CAD groups, among the stable CAD and ACS groups, and between CAD patients with low and high SYNTAX scores (SSs). The 1-year cumulative rate of major adverse cardiac events (MACEs) was also compared among ACS patients by Gal-3 levels. Results: Serum Gal-3 was significantly higher in the CAD group than in the non-CAD group (6.85±6.60 vs 2.73±2.08ng/ml，P <0.001). Furthermore serum Gal-3 was significantly higher in the ACS group than that in the stable CAD group，(8.25±4.87 vs 4.43±3.66 ng/ml，P=0.001). Serum Gal-3 level was an independent predictor of ACS compared with stable CAD group (OR = 1.131, 95% CI: 1.051-1.217, P = 0.001) as well as high SS (OR=1.030, 95% CI: 1.021 1.047, P=0.038) after adjust other confounding risk factors. ACS patients with Gal-3 levels above the median (gal-3=4.78 ng/ml) showed a higher cumulative MACE rate than those with Gal-3 levels below the median. After adjusting other confounding risk factors, Gal-3 remained an independent risk factor for cumulative rate of MACEs in ACS patients( 5.8% higher rate of MACEs incidence per 1ng/ml increment of Gal-3). Conclusion: Gal-3 correlated with the presence of CAD as well as coronary stability and complexity. Gal-3 may be valuable in predicting mid-term prognosis in ACS patients.